2017
DOI: 10.1038/s41524-017-0014-2
|View full text |Cite
|
Sign up to set email alerts
|

Computationally predicted energies and properties of defects in GaN

Abstract: Recent developments in theoretical techniques have significantly improved the predictive power of density-functional-based calculations. In this review, we discuss how such advancements have enabled improved understanding of native point defects in GaN. We review the methodologies for the calculation of point defects, and discuss how techniques for overcoming the band-gap problem of density functional theory affect native defect calculations. In particular, we examine to what extent calculations performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
173
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(193 citation statements)
references
References 89 publications
(132 reference statements)
19
173
1
Order By: Relevance
“…There is a possibility that the defects generated by the Mg ion implantation caused carrier compensation. Since several types of deep-level states have been predicted to be located at the mid-gap and near the valence band, 17 we cannot determine the origin of the observed reduction in the carrier density at this stage.…”
Section: -3mentioning
confidence: 88%
See 4 more Smart Citations
“…There is a possibility that the defects generated by the Mg ion implantation caused carrier compensation. Since several types of deep-level states have been predicted to be located at the mid-gap and near the valence band, 17 we cannot determine the origin of the observed reduction in the carrier density at this stage.…”
Section: -3mentioning
confidence: 88%
“…In a previous report, 16 deep-level states were detected at E C -E = 0.67 eV after N ion implantation with a dosage of 1×10 11 cm -2 (a similar dosage to the present samples), and the density of the deep-level states was found to decrease after subsequent annealing at 900 o C. It was proposed that a possible origin of the deep-level defects was a N interstitial, N i . However, a theoretical study 17 showed that the N i produced an acceptor-like defect level at E C -E = 0.99 eV. If this amount of discrepancy in the energy location is allowed, the following discussion is possible.…”
Section: -3mentioning
confidence: 99%
See 3 more Smart Citations